If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + 1 = 4x + -2(3 + x) Reorder the terms: 2(-3 + x) + 1 = 4x + -2(3 + x) (-3 * 2 + x * 2) + 1 = 4x + -2(3 + x) (-6 + 2x) + 1 = 4x + -2(3 + x) Reorder the terms: -6 + 1 + 2x = 4x + -2(3 + x) Combine like terms: -6 + 1 = -5 -5 + 2x = 4x + -2(3 + x) -5 + 2x = 4x + (3 * -2 + x * -2) -5 + 2x = 4x + (-6 + -2x) Reorder the terms: -5 + 2x = -6 + 4x + -2x Combine like terms: 4x + -2x = 2x -5 + 2x = -6 + 2x Add '-2x' to each side of the equation. -5 + 2x + -2x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 -5 + 0 = -6 + 2x + -2x -5 = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 -5 = -6 + 0 -5 = -6 Solving -5 = -6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (-30(-7))-(210(-3))=840 | | -9x+10y=-19 | | v/7=17.5 | | 4(5n-6)=-4 | | v^2+14v-84=10 | | -5(-6k-4)=-10 | | Sin(x-1)=0.25 | | 2xy+y=36 | | (5x+6)(6x-5)=0 | | -6=-2/9v | | (k-6)(k+8)= | | 8+2x+3-x=2x+1whatisx | | 3z-4=z+0 | | 5x+13=9x-13 | | 5n^2-24n=5 | | -5(7x+7)=-35 | | .5(4x+6)=-6x | | (4x-1)(x-6)=0 | | 7v+1=v | | 0.68+0.45t=1.80t-112 | | -8/9÷16 | | 2(-7-3v)=-4+2(1-2v) | | -7(r+2)=0 | | 2(3x-4)=4(1/2-8) | | 5+10=y | | 3x+4y+5z=4x+7y+6z | | 208=-13n | | a+5+7=3(4+6a)-2(7a+3) | | 3a+7=2x-8b | | 2x-7/4=-8 | | 4x/x-y | | 2/3y=2/9 |